Pseudohomogeneous metallic catalyst based on tungstate-decorated amphiphilic carbon quantum dots for selective oxidative scission of alkenes to aldehyde - Aram Rezaei; Leila Hadian-Dehkordi; Hadi Samadian; Mehdi Jaymand; Homa Targhan; Ali Ramazani; Hadi Adibi; Xiaolei Deng; Lingxia Zheng; Huajun Zheng (Scientific Reports, 2021)
Abstract Herein, we present an interesting role of tungstate-decorated amphiphilic carbon quantum dots (A-CQDs/W) in the selective oxidative cleavage of alkenes to aldehydes. In this work, for the first time, we disclose an unprecedented tungstate-based oxidative system incorporating A-CQDs as a bridge to the homogeneous catalyst for selective and efficient cleavage of a wide substrate scope of alkenes into aldehydes. The A-CQDs/W were synthesized via a one-step hydrothermal synthesis approach using 1-aminopropyl-3-methyl-imidazolium chloride and stearic acid for the surface modification, following by anion-exchange to immobilize WO4 –2 to A-CQDs. The A-CQDs/W act as a pseudohomogeneous metallic catalyst (PMC) for selective oxidative scission of alkenes under phase transfer catalysts (PTC) free condition without over oxidation to acids, using water and H2O2 as a green oxidant. Thanks to the sub-nanometric size and novel engineered chemical structure, this PMC and reactants are in the same phase, besides they can be easily isolated from each other by extraction processes. The synthesized PMC exhibited excellent solubility and stability in various solvents. Interestingly, the system’s high conversion efficiency was preserved even after eight catalytic cycles indicating the recyclability of the synthesized PMC. We believe that this study provides a significant and conceptually novel advance in oxidative cleavage chemistry.